Performance analysis of a stand-alone synchronous reluctance generator under unbalanced conditions - Mostafa Rida; Essam Rashad; Adel El Samahy; Mohamed El Koroflly; Erhab Youssef (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A stand-alone self-excited wind energy conversion system (WECS) is considered commonly used in remote areas due to its simple control and low cost. This paper introduces the performance analysis of a stand-alone self-excited reluctance generator (SERG) under balanced and unbalanced operations. An asymmetrical component is proposed to obtain the positive and negative sequence components of voltages and currents in addition to the unbalanced voltage factor of SERG. The obtained results have been validated and compared with experimental results obtained from a laboratory prototype of a 5.5 kW synchronous reluctance generator driven by a dc motor as a prime-mover under unbalanced excitation capacitors and unbalanced loads. The comparison verifies the applicability of the proposed model.